2015
DOI: 10.1371/journal.pgen.1005164
|View full text |Cite
|
Sign up to set email alerts
|

The UPR Branch IRE1-bZIP60 in Plants Plays an Essential Role in Viral Infection and Is Complementary to the Only UPR Pathway in Yeast

Abstract: The unfolded protein response (UPR) signaling network encompasses two pathways in plants, one mediated by inositol-requiring protein-1 (IRE1)-bZIP60 mRNA and the other by site-1/site-2 proteases (S1P/S2P)-bZIP17/bZIP28. As the major sensor of UPR in eukaryotes, IRE1, in response to endoplasmic reticulum (ER) stress, catalyzes the unconventional splicing of HAC1 in yeast, bZIP60 in plants and XBP1 in metazoans. Recent studies suggest that IRE1p and HAC1 mRNA, the only UPR pathway found in yeast, evolves as a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
173
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(178 citation statements)
references
References 80 publications
(187 reference statements)
3
173
1
1
Order By: Relevance
“…The sgs3-11 (ABRC stock number CS24289), sgs3-13 (SALK_039005), and sgs3-14 (SALK_001394) mutants were obtained from the Arabidopsis Biological Resource Center (ABRC) at The Ohio State University. Screening for homozygousmutation lines was performed essentially as described previously (78,79). Arabidopsis (ecotype Col-0) plants were transformed by the floral-dip method (80).…”
Section: Methodsmentioning
confidence: 99%
“…The sgs3-11 (ABRC stock number CS24289), sgs3-13 (SALK_039005), and sgs3-14 (SALK_001394) mutants were obtained from the Arabidopsis Biological Resource Center (ABRC) at The Ohio State University. Screening for homozygousmutation lines was performed essentially as described previously (78,79). Arabidopsis (ecotype Col-0) plants were transformed by the floral-dip method (80).…”
Section: Methodsmentioning
confidence: 99%
“…One is mediated by IRE1-bZIP60 and is thought to play an essential role in viral infection, whereas the other is mediated by site-1/site-2 proteases (S1P/S2P)-bZIP17/bZIP18), has a similar function to the animal ATF6 pathway and does not play a detectable role in viral invasion (Deng et al, 2011;Gao et al, 2008;Liu & Howell, 2010;Liu et al, 2007;Nagashima et al, 2011;Zhang et al, 2015). The Turnip mosaic virus (TuMV) membrane-associated 6K2 protein is an inducer of bZIP60 splicing, which is necessary for the function of the UPR branch IRE1-bZIP60 in Arabidopsis (Zhang et al, 2015).…”
Section: Bip Bzip60mentioning
confidence: 99%
“…The Turnip mosaic virus (TuMV) membrane-associated 6K2 protein is an inducer of bZIP60 splicing, which is necessary for the function of the UPR branch IRE1-bZIP60 in Arabidopsis (Zhang et al, 2015). It is known that several of these plant RNA viruses induce the UPR in order to benefit their replication and assembly (Yu et al, 2006;Zhang et al, 2015).…”
Section: Bip Bzip60mentioning
confidence: 99%
See 1 more Smart Citation
“…Some external stimuli such as heat stress, salicylic acid treatment, and viral infection have been reported to activate bZIP60 and bZIP28 (Deng et al 2011;Gao et al 2008;Moreno et al 2012;Nagashima et al 2014;Ye et al 2011;Zhang et al 2015). Furthermore, it was reported that an Arabidopsis mutant defective in both IRE1A and IRE1B genes grown under high temperature contains less viable pollen grains, indicating the importance of the UPR in pollen development under high temperature (Deng et al 2016).…”
mentioning
confidence: 99%